Preconception Biomarkers of Allostatic Load and Racial Disparities in Adverse Birth Outcomes: the Bogalusa Heart Study. Issue 6 (10th October 2013) - Wallace, Maeve; Harville, Emily; Theall, Katherine; Webber, Larry; Chen, Wei; Berenson, Gerald
Abstract Background Large disparities in adverse birth outcomes persist between African American and white women in the US despite decades of research, policy, and public health intervention. Allostatic load is an index of dysregulation across multiple physiologic systems that results from chronic exposure to stress in the physical and socio‐cultural environment which may lead to earlier health deterioration among racially or socio‐economically disadvantaged groups. The purpose of this investigation was to examine relationships between maternal biomarkers of allostatic load prior to conception and the occurrence of preterm birth and small for gestational age infants among a cohort of white and African American women participants in the Bogalusa Heart Study. Methods Data from women participants were linked to the birth record of their first‐born infant. Principal components analysis was used to construct an index of allostatic load as a summary of the weighted contribution of nine biomarkers representing three physiologic domains: cardiovascular, metabolic, and immune systems. A series of Poisson regression models based on samples ranging from 1467 to 375 women were used to examine race, individual biomarkers of allostatic load, and quartiles of the allostatic load index as predictors of preterm birth (n = 150, 10.2%) and small for gestational age (n = 135, 9.2%). Results There was no evidence of a relationship between maternal preconception allostatic load and either adverse birth outcome in this sample. Further, there was no evidence of effect modification of by race or education. Conclusions More work is needed in understanding the biological mechanisms linking social inequities to racial disparities in adverse birth outcomes.